'Returnees' and political poetry in Western Sahara: defamation, deterrence and mobilisation on the web and mobile phones. Issue 4 (7th August 2016) - Boulay, Sébastien
ABSTRACT: This paper explores the relationships between literature, migration and politics in Western Sahara, in a context of a four-decade decolonisation conflict. Since a few years, some Polisario Front personalities have been rallying the Moroccan 'side' and have aroused the production and circulation, on the web and the mobile phones, of a new kind of satirical poetry targeting these 'ralliés' considered as betrayers of the independence cause. This sensitive literature, whether funny or violent, rare but successful, amuse and disturb Sahrawi audiences, provokes poetic responses, create new debate opportunities and allow social sciences to better understand how politicians from both parties try to exploit and/or control population movements in that area and how people live and manoeuvre around these policies.